2011
DOI: 10.1002/mats.201100076
|View full text |Cite
|
Sign up to set email alerts
|

Kinetic Modeling of ICAR ATRP

Abstract: Kinetic modeling is used to better understand and optimize initiators for continuous activator regeneration atom‐transfer radical polymerization (ICAR ATRP). The polymerization conditions are adjusted as a function of the ATRP catalyst reactivity for two monomers, methyl methacrylate and styrene. In order to prepare a well‐controlled ICAR ATRP process with a low catalyst amount (ppm level), a sufficiently low initial concentration of conventional radical initiator relative to the initial ATRP initiator is requ… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

9
91
0

Year Published

2013
2013
2022
2022

Publication Types

Select...
8

Relationship

3
5

Authors

Journals

citations
Cited by 83 publications
(100 citation statements)
references
References 53 publications
9
91
0
Order By: Relevance
“…To reach a conversion of 0.90 only 2 h are needed at 10 ppm, whereas already 16 h are required in case 50 ppm is employed. In agreement with previous deterministic simulations on ICAR ATRP homopolymerization [22], too low ppm levels lead to FRP behavior, as a sufficient amount of deactivator is needed to ensure controlled activation-growth-deactivation cycles. For an initial Cu(II) amount of 10 ppm, as shown in Figure 4, the ATRP catalyst is mostly in its activator state and an almost zero deactivator concentration is obtained at high conversion.…”
Section: Batch Proceduressupporting
confidence: 90%
See 2 more Smart Citations
“…To reach a conversion of 0.90 only 2 h are needed at 10 ppm, whereas already 16 h are required in case 50 ppm is employed. In agreement with previous deterministic simulations on ICAR ATRP homopolymerization [22], too low ppm levels lead to FRP behavior, as a sufficient amount of deactivator is needed to ensure controlled activation-growth-deactivation cycles. For an initial Cu(II) amount of 10 ppm, as shown in Figure 4, the ATRP catalyst is mostly in its activator state and an almost zero deactivator concentration is obtained at high conversion.…”
Section: Batch Proceduressupporting
confidence: 90%
“…Except for reactions involving conventional radical initiator fragments, these intrinsic parameters are taken from a previous kinetic study on the related "normal" ATRP system [26]. For simplicity, a constant conventional radical initiator efficiency of 0.70 [22] is used and the activation/deactivation kinetic parameters related to the conventional radical initiator are taken equal to those of the secondary species. As indicated in a recent study on ICAR ATRP of styrene, it can be expected that these parameters have a very limited effect on the overall polymerization rate and control over polymer properties [27], justifying the previous assumption.…”
Section: Kinetic Modelmentioning
confidence: 99%
See 1 more Smart Citation
“…is the number-average chain length as defined by Equation (19). Also, ʋ is the free volume fraction, which is related to polymer concentration (Equation (25)) [29,30],…”
Section: Diffusion-controlled Reactionsmentioning
confidence: 99%
“…Recent simulations [55] have shown that in ICAR ATRP the control over polymerization rate and polymer properties can be directly manipulated by adjusting the polymerization conditions. For instance, it was demonstrated that, depending on the ATRP catalyst reactivity, step-wise addition of conventional radical initiator in the ICAR ATRP of methyl methacrylate and styrene is needed to reach high conversion while still obtaining a good livingness and control over chain length with ppm levels of ATRP catalyst.…”
Section: Introductionmentioning
confidence: 99%